2001
DOI: 10.2174/0929867013372959
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer and Oxidative Stress as Key Factors in the Design of Drugs Selectively Active in Hypoxia.

Abstract: Hypoxia is a feature of some regions of many tumours, ischaemic events, and arthritis. Drugs activated in hypoxia have wide potential application, particularly in overcoming the resistance of hypoxic tumour cells to radiotherapy. Key features of such drugs include redox properties appropriate for activation by reductase enzymes (typically flavoproteins), and oxygen-sensitive reduction chemistry such that normal levels of oxygen inhibit or reverse reduction. In many cases this selectivity is achieved by a fast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 141 publications
(206 reference statements)
1
112
0
1
Order By: Relevance
“…The conversion of the nitro substituent of KS119 to a hydroxylamino group probably begins with the input of a single electron, followed by protonation and disproportionation and further reduction as described by Knox et al (16); thus, the initiating enyzmes are one-electron-reducing systems. Under aerobic conditions the input of the initial electron produces the nitro radical anion, which is rapidly scavenged by oxygen (15). This phenomenon results in redox cycling that regenerates the parental prodrug and forms superoxide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of the nitro substituent of KS119 to a hydroxylamino group probably begins with the input of a single electron, followed by protonation and disproportionation and further reduction as described by Knox et al (16); thus, the initiating enyzmes are one-electron-reducing systems. Under aerobic conditions the input of the initial electron produces the nitro radical anion, which is rapidly scavenged by oxygen (15). This phenomenon results in redox cycling that regenerates the parental prodrug and forms superoxide.…”
Section: Discussionmentioning
confidence: 99%
“…Under aerobic conditions, the nitro radical anion is rapidly back-oxidized by O 2 to regenerate the inactive prodrug form and O 2 ⅐ÏȘ , resulting in an undetectably low steadystate concentration of nitro radical anions (15). However, under hypoxic conditions, the nitro radical anion probably undergoes disproportionation and further reduction through the addition of successive electrons to produce nitroso, hydroxylamino, and amino species, as demonstrated by p-substituted nitrobenzenoids (16).…”
Section: -(2-chloroethyl)-2-[[1-(4-nitrophenyl)ethoxy]carbonyl]hydramentioning
confidence: 99%
“…The D mcl values for urea were determined by fitting the flux data to MCLs for which thicknesses were subsequently determined by microscopy, expanding on previous determinations. [38] The urea D mcl values (mean ± s.e.m., [n], cm 2 s −1 × 10 7 ) were 4.50 ± 0.23 [6] for HT29, 9.62 ± 0.85 [9] for SiHa, 1.31 ± 0.37 [15] for HCT8-Ea, and 26.8 ± 0.72 [13] for HCT8-Ra. Flux through bare support membranes was also evaluated for each compound to confirm stability and to check that diffusion coefficients through the support membrane (porosity 11%) were consistent with MW.…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…[10] At the same time the presence of more severe and extensive hypoxia in tumours than in normal tissues provides a physiological target that can potentially be exploited as a basis for tumour selectivity. [3,[11][12][13][14][15][16] Several prodrugs that are selectively activated under hypoxia are currently in clinical or preclinical development, [17][18][19][20] including the benzotriazine-di-N-oxide tirapazamine (TPZ; Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Studies of the antitumor properties and mechanisms of action of quinone derivatives have shown that they can act as topoisomerase inhibitors via DNA intercalation, and their toxicity can also be explained by oxidative stress with reactive oxygen species (ROS) generation, which are usually toxic to normal tissues, thus reducing the therapeutic utility of quinones. [3][4][5] Despite recent technological advances, cancer treatment remains a challenge, and, in some circumstances, a complete remission is difficult to achieve. Currently, the investigation of natural products and chemical modifications to antitumor substances are among the most important strategies used in the search for new antineoplastic drugs.…”
mentioning
confidence: 99%